Implementasi Aplikasi Sistem Pakar Untuk Deteksi Kerusakan Mesin Kendaraan Sepeda Motor Menggunakan Metode Case-Based Reasoning Berbasis Website Pada Bengkel Bams Motor - Khairullah Tulfah; Bani (OKTAL : Jurnal Ilmu Komputer dan Sains, 2025)
The development of information technology has had a significant impact in the automotive field, particularly in improving workshop services. Motorcycle workshops often face challenges in the manual diagnosis process of engine damage, which takes considerable time and is prone to errors. Based on these issues, this study aims to design and develop a web-based expert system application to assist in detecting motorcycle engine damage. The system applies the Case-Based Reasoning (CBR) method with four stages: Retrieve, Reuse, Revise, and Retain to provide solutions based on previous cases. The development method used is Rapid Application Development (RAD), consisting of planning, design, implementation, and testing stages. The application was developed using PHP programming language and MySQL database, and deployed on a local XAMPP server. The results of the black box testing show that all features function properly. This application enables a faster and more accurate diagnosis process, assisting both mechanics and users in identifying the right repair solutions.